A Meta-Analysis of Students' Perceptions on the Readability of Learning Materials in TEFL Classes: Are Original Textbooks Effective? - Handayani, Sri (International Journal of Education and Humanities, 2024)
This study aimed to describe students' perceptions of the readability of learning materials in the Method of Teaching English as a Foreign Language course. The study addresses the issue of how students perceive the readability of the instructional materials they use. This qualitative research investigates the phenomenon of students' perceptions holistically, presenting the results in the form of words and sentences. Thirty-eight students from two classes enrolled in the Method of Teaching English as a Foreign Language course this semester were selected as the research subjects. To collect qualitative data, questionnaires, interviews, and observations were employed. The collected data were then analyzed using descriptive qualitative research methods, which include data collection, data reduction, data display, and drawing conclusions. The results of the study indicate that the majority of students have a positive perception of the readability of the learning materials used. Students felt that the instructional materials were easy to understand and helped them grasp the concepts being taught. However, some students pointed out that certain parts of the materials were too complex and required further explanation. Based on these findings, it is recommended that instructors take into account student feedback regarding the instructional materials and make adjustments as necessary. Instructors are also advised to provide additional explanations or supplementary materials for sections that students find challenging. Furthermore, it is crucial for instructors to continuously evaluate and update the learning materials to ensure they remain relevant and easily accessible to all students. By doing so, the learning process can be more effective and efficient